Praktik Poligami Masyarakat Kalisat Rembang Pasuruan Tinjauan dalam Perspektif Teori Behavior - Solikin, Nur (Islamika Inside: Jurnal Keislaman dan Humaniora, 2021)
Abstract: This study examines the practice of polygamy in the Kalisat community from the point of view of behavior theory. The two main questions to be answered in this paper are about views the Kalisat community about polygamy and the process of polygamy in the perspective of behavior theory which places the actor's actions as being affected by the stimulus and then it becomes a new stimulus for the continuation of the practice of polygamy. Through behavior theory as a study tool, this study concludes that polygamy in the perception of the Kalisat community is no different from the view of the majority of jurists who say that polygamy is permissible on the condition that there is justice in it, regardless of what justice is demanded, whether in the material or immaterial fields. Another conclusion, the practice of polygamy carried out by the Kalisat community, on the one hand as acknowledged by one of the informants is a trait that has been passed down from generation to generation, on the other hand, it is also closely related to the community environment which has considered polygamy as a normal thing and therefore they Those who do not have polygamy are considered as "husbands who are afraid of their wives".